Strategic Ownership Dynamics: Unveiling the Impact of Business Strategy and Performance on LQ 45 Manufacturing Stock Prices - Junianto, Prima Ayu Novita; Utama, Anak Agung Gde Satia (APSSAI, 2024)
Research aims: This study delves into the intricate dynamics between business strategy, corporate performance, and managerial ownership structure, and their collective impact on stock prices within the manufacturing sector of the LQ 45 index from 2019 to 2023. By juxtaposing State-Owned Enterprises (SOEs) with non-SOEs, this research uncover nuanced insights into how strategic decisions and ownership configurations influence market valuation. Design/Methodology/Approach: This research presents comprehensive analysis employs robust quantitative methods, incorporating financial metrics, performance indicators, and stock price movements to draw correlations and infer causations. Research findings: The findings highlight distinct patterns and discrepancies between SOEs and Non-SOEs, emphasizing the pivotal role of ownership structure in shaping strategic effectiveness and market perception. Theoretical contribution/Originality: The theoretical contribution of this study lies in its exploration of the interplay between business strategy, corporate performance, and managerial ownership structure within the context of the manufacturing sector in Indonesia, specifically focusing on the LQ 45 index from 2019 to 2023. Practitioner/Policy implication: This study not only contributes to the existing body of knowledge but also provides actionable insights for investors, policymakers, and corporate leaders aiming to optimize strategic frameworks and enhance shareholder value in the competitive landscape of the Indonesian manufacturing industry.